2017
DOI: 10.1016/j.yjmcc.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Selective coupling of the S1P 3 receptor subtype to S1P-mediated RhoA activation and cardioprotection

Abstract: Sphingosine-1-phosphate (S1P), a bioactive lysophospholipid, is generated and released at sites of tissue injury in the heart and can act on S1P1, S1P2, and S1P3 receptor subtypes to affect cardiovascular responses. We established that S1P causes little phosphoinositide hydrolysis and does not induce hypertrophy indicating that it does not cause receptor coupling to Gq. We previously demonstrated that S1P confers cardioprotection against ischemia/reperfusion by activating RhoA and its downstream effector PKD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 65 publications
(100 reference statements)
3
40
0
Order By: Relevance
“…1D). We previously demonstrated that the S1PR 3 is the S1P receptor subtype that selectively couples to RhoA activation in cardiomyocytes [10], and show here that the S1PR 3 specific agonist CYM-51736 also increases phosphorylation of Drp1 at serine-616 (Fig. 1E), a response abolished by functional inhibition of RhoA signaling with C3.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…1D). We previously demonstrated that the S1PR 3 is the S1P receptor subtype that selectively couples to RhoA activation in cardiomyocytes [10], and show here that the S1PR 3 specific agonist CYM-51736 also increases phosphorylation of Drp1 at serine-616 (Fig. 1E), a response abolished by functional inhibition of RhoA signaling with C3.…”
Section: Resultssupporting
confidence: 70%
“…Our findings with expression of active RhoA are recapitulated by GPCR stimulation with S1P or an S1PR 3 agonist, both of which we have shown to lead to activation of RhoA [9, 10]. Both agonists increase phosphorylated Drp1 in a RhoA/ROCK dependent manner.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations